Religious Discourse of Biblical Intertextuality in Abraham Regelson Works: Selected Samples from the Collection "House of Brightness": הנאום הדתי של האינטרטקסטואליות התנ''כית ביצירותיו של אברהם רגלסון סיפורים נבחרים מקובץ "בית הניצוץ" (Journal of the College of Languages (JCL), 2019)
This research display a selected sample of Regelson's texts, there were interrelations and interactions unfolded so as to show his creativity in the employment of religious texts. In the story "In the Youth of Moses", he inter-texted the episode of the Prophet Moses from the Torah, the Source of legislation, to signify a legislative issue needed by the community. As for the story of "Samson, One of the Falling", he originated the character of The Judge Samson by alluding to the Book of the Judges, which is the Book which reminded of the defeat and slavery of the Palestinians by a Jewish leader, as is related in Jewish religious texts. Further, and the story of "And Haman Said", he chose the story of the Queen Esther from the Book of Esther so as to pick up the dialogue of the King with his minister, and to personify the assaults made by nations on the Jews in accordance with the writer's racist thinking.תקצר הנאום הדתי הוא תחום רעיוני ביצירות הספרותיות הישנות והחדשות; הייחוד של הטקסט הספרותי מהטקסטים האחרים הוא במה שנושא בתוכו מנאום אנושי או דתי או פוליטי, ולנאום הדתי יש צורך לאינטרטקסטואליות מטקסטים קדושים, הם מעודדים את מחשבתו של הסופר, וגם הם מהפיכים היצירה משוכנעת ומושפעת יותר, ולכן הסופר אברהם רגלסון לקח מהתנ''ך לחלק מסיפוריו בקובץ "בית הניצוץ" כדי שמחזק דעתו במחשבות שנמצאים ביצירות האלה. נבחר הסיפורים שחקרתי אותם נחשפו את ההשפעות והציטוטים התנ''כיים ביצירה, וגם התגלה את כשרונו של המספר בהשתמשות הטקסטים הקדושים וגם את משמעותם השלילית, הוא לקח את המשמעויות והצורות והאירועים שמאמצים האלימות נגד הערבים. האינטרטקסטואליות של רגלסון הייתה החזרה נפשית להיסטוריה היהדות למען פירוש המציאות הקשה שנמצאים היהודים בה, והוא נאלץ לשכנע עצמו והקורא לקבל אותה. גם הייתה אינטרטקסטואליות לשונית ומשמעותית מהתנ''ך בדמויות והאירועים, יתר על כן הוא עיצב אותם ליצור מראהו החדש שמתאים עם מחשבותיו.